Pioneers of television [videorecording (DVD)] - Boettcher, Steven J.; Trinklein, Michael J.; Saperstein, Harlan; Jones, Jack (PBS Home Video ; Distributed by Paramount Home Entertainment, 2008)
This four-part series features sitcoms and archival clips to offer a fresh take on the first celebrities of television, including interviews with several of them.